2020
DOI: 10.3390/antiox9090774
|View full text |Cite
|
Sign up to set email alerts
|

Human Relaxin-2 (Serelaxin) Attenuates Oxidative Stress in Cardiac Muscle Cells Exposed In Vitro to Hypoxia–Reoxygenation. Evidence for the Involvement of Reduced Glutathione Up-Regulation

Abstract: Serelaxin (RLX) designates the pharmaceutical form of the human natural hormone relaxin-2 that has been shown to markedly reduce tissue and cell damage induced by hypoxia and reoxygenation (HR). The evidence that RLX exerts similar protective effects on different organs and cells at relatively low, nanomolar concentrations suggests that it specifically targets a common pathogenic mechanism of HR-induced damage, namely oxidative stress. In this study we offer experimental evidence that RLX (17 nmol L-1), added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…These data open exciting avenues of study to more fully understand RLX's effects in the heart to suppress arrhythmia, as the data hint that RLX may prevent the deleterious cardiac phenotypes in PAH through multiple pathways, which may include the restoration of the redox state as evidenced by RLX-mediated reversal of upregulated Nrf2 and GST in PAH hearts. This interpretation is consistent with the GSH up-regulation in H9C2 rat cardiac cells by RLX following hypoxia-reoxygenation ( 32 ), and a reduction in oxidative stress by RLX in a swine ischemia-reperfusion model ( 33 , 34 ). Hence, the rescue of VT/VF and arrest by DTT implied that PAH hearts had compromised glutathione metabolism and REDOX balance, which was prevented by RLX.…”
Section: Discussionsupporting
confidence: 85%
“…These data open exciting avenues of study to more fully understand RLX's effects in the heart to suppress arrhythmia, as the data hint that RLX may prevent the deleterious cardiac phenotypes in PAH through multiple pathways, which may include the restoration of the redox state as evidenced by RLX-mediated reversal of upregulated Nrf2 and GST in PAH hearts. This interpretation is consistent with the GSH up-regulation in H9C2 rat cardiac cells by RLX following hypoxia-reoxygenation ( 32 ), and a reduction in oxidative stress by RLX in a swine ischemia-reperfusion model ( 33 , 34 ). Hence, the rescue of VT/VF and arrest by DTT implied that PAH hearts had compromised glutathione metabolism and REDOX balance, which was prevented by RLX.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the effects of RLX on DHE-staining-associated superoxide and TGF-β1 expression levels did not appear to be mediated via a P2X7R-dependent mechanism (Figure 6), since the DHE-staining-or TGF-β1-inhibitory effects of RLX were not significantly affected by A-438079 co-administration. These findings may have suggested that the ROS-inhibitory effects of RLX, which were blocked by NAC co-administration, may have more likely involved its ability to restore glutathione levels [50] and/or inhibit the detrimental effects of hydrogen peroxide or other oxidative stress-related metabolites [51,52], rather than regulate superoxide levels. Furthermore, the lack of a marked effect of A-438079 on the RLX-induced down-regulation of TGF-β1 expression levels may have suggested that the crosstalk between RXFP1 and the P2X7R may have more likely occurred at the cellular level (i.e., on macrophages and/or myofibroblasts that express both receptors and the NLRP3 inflammasome), rather than on the cytokines produced by these cells.…”
Section: Discussionmentioning
confidence: 99%
“…NHCF-A were seeded in 24-multiwell plates at the same confluence as for the wound-healing assays. After serum-deprivation for 8 h, cells were treated with RLX2 at a dose of 1 ng/mL 35 , 54 , 64 , or with vehicle (PBS) (condition = 3 biological replicates × 4 technical replicates) for 24 h. At the end of the process, cells were lysed for the determination of collagen type I alpha 2 chain ( COL1A2 ), discoidin domain receptor tyrosine kinase 2 ( DDR2 ), platelet derived growth factor receptor alpha ( PDGFRα ), periostin ( POSTN ), alpha smooth muscle actin ( αSMA), transforming growth factor β1 ( TGF-β1 ), vimentin ( VIM ) and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) levels. Moreover, mRNA expression of fibronectin extra domain A ( FN-EDA ) and myosin heavy chain 10 ( MYH10 ) were determined in order to phenotype NHCF-A cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were serum-deprived for 8 h prior to the beginning of the experiment. Using a plastic pipette tip, a wound field was created with a defined gap of 1 mm in each well, and cells were then treated with RLX2 at 1 or 10 ng/mL, or vehicle (phosphate-buffered saline (PBS)) (n = 6 biological replicates × 4 technical replicates), as previously described 35 , 54 , 64 , without fetal bovine serum (FBS) to inhibit cell proliferation and to allow cell migration. Random fields were photographed with a Leica DMI6000B Automated/Motorized Inverted Microscope (Leica Microsystems, DE) during the time-course procedure.…”
Section: Methodsmentioning
confidence: 99%